Montado Intangible Heritage in Southern Portugal - Batista, Teresa (2017)
The montado is a highly valuated biocultural landscape, typical of the Iberian Peninsula Southwest, traditionally related with agro-forestry-pastoral systems where open formations of scattered cork, holm or mix oaks compose the arboreous layer under which a rotation of crops/fallows/pastures is practiced. This aesthetically pleasing and biologically rich landscape, nowadays protected by Portuguese and European Law, is a type of continuing landscape, according to the World Heritage Convention classification. It provides not only important environmental functions and services but also cultural ones, in particular the heritage which includes natural structures as well as tangible and intangible cultural elements. The montado intangible heritage values should be emphasized: cork and wood craftworks; gastronomy; local traditions and knowledge as oaks pruning, cork harvesting and folk medicine; beliefs and legends related with religious events, agro-pastoral works or megalithic monuments and traditional artistic activities. The development of this intangible heritage can boost local socio-economic sustainability.